PIDD mediates the association of DNA-PKcs and ATR at stalled replication forks to facilitate the ATR signaling pathway. Issue 4 (4th January 2018) - Lin, Yu-Fen; Shih, Hung-Ying; Shang, Zeng-Fu; Kuo, Ching-Te; Guo, Jiaming; Du, Chunying; Lee, Hsinyu; Chen, Benjamin P C
Abstract: The DNA-dependent protein kinase (DNA-PK), consisting of the DNA binding Ku70/80 heterodimer and the catalytic subunit DNA-PKcs, has been well characterized in the non-homologous end-joining mechanism for DNA double strand break (DSB) repair and radiation resistance. Besides playing a role in DSB repair, DNA-PKcs is required for the cellular response to replication stress and participates in the ATR-Chk1 signaling pathway. However, the mechanism through which DNA-PKcs is recruited to stalled replication forks is still unclear. Here, we report that the apoptosis mediator p53-induced protein with a death domain (PIDD) is required to promote DNA-PKcs activity in response to replication stress. PIDD is known to interact with PCNA upon UV-induced replication stress. Our results demonstrate that PIDD is required to recruit DNA-PKcs to stalled replication forks through direct binding to DNA-PKcs at the N' terminal region. Disruption of the interaction between DNA-PKcs and PIDD not only compromises the ATR association and regulation of DNA-PKcs, but also the ATR signaling pathway, intra-S-phase checkpoint and cellular resistance to replication stress. Taken together, our results indicate that PIDD, but not the Ku heterodimer, mediates the DNA-PKcs activity at stalled replication forks and facilitates the ATR signaling pathway in the cellular response to replication stress.